The Role of Mandarin in Indonesia's Tourism Sector - Adi, Dian Prasetyo; Rinada, Ayu (International Journal of Culture and Art Studies, 2020)
Indonesia is well-known for its natural beauty and cultural diversity. This becomes an extraordinary attraction for Indonesian tourism sector in which the government has also put their attention to. Tourists from others counties like to visit Indonesia. They speak in many international languages, include Mandarin. However, there are still fewer human resources who respond to it. The skill that must be possessed to prepare and improve a good image for tourists is the mastery of Mandarin. Tourism agencies who should have mastered Mandarin include travel agents, hotel employees, tour guides, and tourism practitioners. The minimum target for mastering Mandarin languages covers: simple conversations related to the work done, as well as the mastery of basic grammar and conversations. The mastery of Mandarin, as well as the understanding of the culture of Chinese tourists, is expected to provide maximum service and to create a good impression or image that improves the Indonesian tourism industry.